Measuring Vulnerability of Marine and Coastal Habitats’ Potential to Deliver Ecosystem Services: Complex Atlantic Region as Case Study - Willaert, Tom; García-Alegre, Ana; Queiroga, Henrique; Cunha-e-Sá, Maria A.; Lillebø, Ana Isabel (Frontiers in Marine Science, 2019)
The main objective of this work is to promote Ecosystem Based Management (EBM) using a complex Atlantic region to demonstrate how InVEST model tool and associated methods can be applied to calculate benthic habitats cumulative risk and create a vulnerability index of the potential of these habitats to deliver ecosystem services (ES). The study area, in the Western-Atlantic coast of Portugal, includes the Nazaré Canyon (> 3000m depth within the study region), Óbidos Lagoon (transitional waters), São Martinho do Porto bay (marine inlet), and Berlengas Archipelago (UNESCO world biosphere reserve). The ES delivered by this complex coastal region support the main regional/local socio-economic activities (e.g. fisheries and tourism activities). The approach combined the InVEST habitat risk assessment tool with the identified ES to create a proxy for the habitats’ vulnerability to deliver ES. Within the region twenty eight marine benthic habitats were identified and combined with twelve classes of ES (Common International Classification of ES), and two prospective scenarios were analysed (a potential socio-economic scenario for 2025 and a climate change scenario for the end of the century). The results show that the applied vulnerability approach enables the combination of information from different sources, including local knowledge, and the translation of the generated information into 2D spatial explicit maps that can support management strategic options, namely in the context of maritime spatial planning and ‘Blue Growth’. The interpretation of the habitat vulnerability approach requires taking into account data spatial resolution, its quality and the impact of associated pressures. However, despite the limitations and assumptions (e.g. all ES classes are equally important), models such asthis have opened new avenues contributing to improve EBM, by combining spatial explicit GIS tools with supply and demand of marine ES, human activities and their related positive and negative impacts.